Entre o sonoro e o visual: relações e processos nas artes - Codevilla, Fernando Franco [UNESP] (2015)
This thesis proposes a discussion about the relationship between sound and image in the fild of Sound and Visual Arts. In this way, we realize a mapping of artists consid- ering some manifestations such as Visual Music, Sound Sculptures, Graphic Notation, Paintings, Concrete Poetry, Cinema and Multimedia with electronic and digital re- sources. We observe in the works of the artists, how operations with materials occur, identifying the means and techniques that give forms to the works. It is also relevant to consider the context in which the works are inserted, as they are a reflction of their spacetime realization, being therefore in sync with the other factors determining each realization, such as the scientifi, technological and cultural contexts. In these inter- sections between the contexts, we verify the existence of other similarities involving the works, such as the relation between art and science, since several works are developed from scientifi concepts, or are produced through collaboration between art- ists, scientists and engineers, or still, in more recent studies, it is common to fid works elaborated with the same means that are used in scientifi research. Hence, we focus in the functionality of the artists and treat the sound and visual elements as materi- als that are used in the formative processes of the artworks. With these principles, we are interested in discovering the ways of establishing relationships between sound and image.